Audible Image Description as an Accommodation in Statewide Assessments for Students with Visual and Print Disabilities. (July 2017) - Ferrell, Kay Alicyn; Correa-Torres, Silvia M.; Howell, Jennifer Johnson; Pearson, Robert; Carver, Wendy Morrow; Groll, Amy Spencer; Anthony, Tanni L.; Matthews, Deborah; Gould, Bryan; O'Connell, Trisha; Botsford, Kathryn D; Dewald, Hong Phangia; et al.
Introduction: Although image description has been identified as an accommodation for presentations conducted in the classroom, only a few U.S. states have approved it for use in high-stakes assessments. This study examined the use of audible image description as an assessment accommodation for students with visual and print disabilities by investigating student comprehension under multiple conditions. Methods: Students in three western states in grades three through eight who had visual ( n = 117) or print ( n = 178) disabilities participated in an abbreviated test constructed of retired assessment questions in English language arts, mathematics, and science, that were aligned with each state's instructional standards, under conditions with and without standardized description of graphic images. The study used a within-subjects block design to collect and compare comprehension data under conditions where audible image description was both used and not used in an abbreviated test. Results: Results indicated that students who read braille were more likely to respond correctly under the audible image description condition, and students with visual and print disabilities who used print were equally likely to respond correctly regardless of condition. Discussion: Braille readers were more likely to obtain a correct answer when audible image description accompanied the question. Audible image description did not affect the likelihood of a correct response from students with print disabilities or students with visual disabilities who read print. Implications for practitioners: Audible image description is an accommodation that may help braille readers perform better on tests. Although the Partnership for Assessment of Readiness for College and Careers (PARCC) and Smarter Balanced consortia are taking steps to include image (or picture) descriptions in their assessment accommodations, teachers may want to develop a standard method for describing images and familiarize their braille readers to the strategy by including it in instruction and in classroom tests. Readers are referred to the National Center on Accessible Media's online guidelines for image description.